(untitled) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
This pitonan tradition is intended for children who are setting their feet on the ground for the first time. In the implementation of this tradition there are many symbols such as climbing the jadah, climbing stairs made of sugar cane, entering a chicken cage, bathing using setaman flowers, spreading udhik-udhik and cutting tumpeng. This tradition is usually carried out when the baby is 7 months old on the Javanese calendar. This 7 month old baby is usually marked by starting to crawl. Based on this background, several problems were formulated as follows: 1) What is the form of the pitonan tradition in Ringinpitu Village, 2) What is the function of the pitonan tradition in Ringinpitu Village, 3) What is the meaning of Hindu philosophy contained in the pitonan tradition in Ringinpitu Village. Researchers use 2 theories to dissect existing problem formulations as follows: 1) Religious Theory, 2) Symbol Theory. The form of the Pitonan tradition consists of the following: the time for implementing the Pitonan tradition is carried out when the baby is 7 months old, marked by the baby starting to crawl, in the procession of implementing the Pitonan tradition, it goes through several stages such as undressing, climbing stairs, entering the chicken cage, bathing in setaman flower water and papacan, kenuren. The Pitonani tradition also uses several facilities such as chicken cages, setaman flower water, sugar cane ladders, chicken ingkung, various rice and accompaniments, various porridge and market snacks, plantains, cok bakal, coins and yellow rice, and jadah. Apart from being used to save babies, the Pitonan tradition also functions as a means of strengthening relationships between relatives and also functions as a cultural preservation. This tradition also contains many moral values such as respecting parents and loving God’s animals. In the implementation of the Pitonan tradition, several facilities are required to be seven, such as the stairs to be climbed have seven steps which describe the level of life and education that will be passed, apart from that there are also seven jadah where each color has its own meaning, then The water and flowers used to bathe the child each come from seven springs and seven types of flowers